Syukur dan Pujian menurut Muhammad Shaleh Darat As-Samarani: Kajian atas QS. Al-Fatihah [1]:[2] Tafsir Faidh Ar-Rahman - Baihaki, Egi Sukma (Sekolah Tinggi Filsafat Islam Sadra, 2016)
Praise and gratitude (syukr) are closely related to forms of worshiping of a servant to his Lord. Many verses of the Qurâan show this as it is associated with favors that God has bestowed upon His creation. However, there are still many people who neglect and forget to thank and praise God for all the blessings that God has given to them. Either becauseÂ ofÂ theirÂ ownÂ humiliation,Â asÂ wellÂ asÂ theÂ weaknessÂ ofÂ thoseÂ whoÂ areÂ unable to understand the nature of gratitude and praise itself. This article will see how this message appears in (QS. al-FÄtiáºah [1]: 2) where Allah orders his worshipers to thank andÂ praiseÂ him,Â whileÂ GodÂ HimselfÂ WhoÂ startedÂ praisingÂ Him.Â Therefore,Â theÂ aim of this paper is to introduce how such views and ideas appear through Muhammad Sholeh Darat al-Samarani, mainly when interpreting (QS. al-FÄtiáºah [1]: 2) in his book, TafsÄ«r Faidh al-RaáºmÄn.